The Urgency of Establishing a Business Competition Court in Indonesia - Bayuaji, Rihantoro (KnE Social Sciences, 2023)
Fair law enforcement in handling the business competition complications in Indonesia is essential to promote a conducive business competition climate and to ensure the enforcement of Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. The legal system in the business competition court in Indonesia cannot be separated from the role of KPPU as an institution with the function of regulating and monitoring competition behavior. KPPU, in the context of law enforcement on business competition complications, has the authority to conduct an investigation and adjudicate on the competition disputes in a judicial institution organized by KPPU. Analyzing the authority of KPPU starting from the process of an investigation until the adjudication to business competition cases is a matter that needs to be studied in the corridor of its independence. KPPU’s authority in conducting the investigation and the adjudication needs to be studied more specifically, especially in its function to ensure a sense of justice and impartiality for business actors as the accused parties in a dispute. This study aims to assess the urgency of establishing a business competition court in Indonesia. For this reason, the research methods used were the statutory approach and the conceptual approach. This research has a potential significance to be used as the material in making the amendment for the competition law in Indonesia to urge the Government and Judiciary to form an independent business competition court. Keywords: Business competition; competition law; KPPU